The Occurrences of Sexual and Gender Based Violence in Wajir County, Kenya - Hafsa, Ibrahim A.; Wario A., Halkano (African Journal of Education,Science and Technology (AJEST), 2022)
Gender Based Violence (GBV) against women and girls is a sensitive and global phenomenon, which is also a major economic, social health and security concern for the affected communities around the globe. Women and girls in Wajir County are an easy target due to the socio-economic and cultural set up, this was exacerbated by the Covid-19 outbreak. The Covid-19 control measures by the Ministry of Health of lockdowns, closure of learning institutions and curfews contributed immensely to the increased cases of violence against women and girls especially from known perpetrators. There are a lot of stakeholders and key partners in dealing with the menace and their efforts are gaining momentum. The study employed a mixed method approach. Three sub-counties were randomly selection from the six sub counties found in Wajir County. The target population for this study were female and male members of the community aged between 18 – 64 years. A total sample was 1,250 were sampled. Data was corrected through questionnaires, interviews and focused group discussion. Collected data was analysed using SPSS and results were presented descriptively and qualitative data was analysed using narrative analysis. In Wajir county GBV manifests itself mainly in the form of sexual violence; FGM, early marriages, rape, incest and defilement and the most common of them all being rape and defilement. This is mainly propagated by bad cultural practices, poverty, lack of proper education and advocacy on SGBV. To maintain the sustainability and efficacy of the fight against GBV and sexual assault within communities, national and international funding programmes administered by local NGOs and community women's groups is necessary.